Psychological Well-Being of Early Adult K-Pop Fans Across Demographic Groups: Gambaran Psychological Well-Being Dewasa Awal Penggemar K-Pop Berdasarkan Demografi - Elmiah Fadillah Afrizal Afrizal; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Psychological well-being reflects the realization of an individual’s psychological potential through self-acceptance, positive relationships, autonomy, environmental mastery, purpose in life, and personal growth. Specific Background: K-pop fandom has become increasingly prevalent among Indonesian young adults and may provide both beneficial and maladaptive experiences that are associated with psychological well-being. Knowledge Gap: Although previous studies have examined the relationship between celebrity worship and psychological well-being, empirical descriptive evidence on the psychological well-being profile of early adult K-pop fans across demographic characteristics remains limited. Aims: This study aimed to describe the psychological well-being of early adult K-pop fans and to compare psychological well-being across gender, marital status, and employment status. Results: Using a descriptive quantitative design, data were collected from 230 early adult K-pop fans using a reliable Psychological Well-Being Scale (α = 0.865). Most participants (67%) were in the moderate category, 17% were in the high category, and 16% were in the low category. Positive relations with others and personal growth were prominent in the high category, whereas self-acceptance and autonomy were dominant in the moderate category. ANOVA indicated significant differences based on marital status and employment status, but no significant differences based on gender. Novelty: This study provides a demographic-based profile of psychological well-being among early adult K-pop fans in Indonesia. Implications: The findings support the development of community counseling and mental health interventions tailored to K-pop fandom populations. Highlights: Most early adult K-pop fans demonstrated moderate levels of psychological well-being. Marital status and employment status were associated with significant differences in well-being scores. Positive relations and personal growth characterized participants in the high well-being category. Keywords: Psychological Well-Being, Early Adulthood, K-Pop Fans, Demographic Characteristics, Mental Health